High - talent manpower for science and industry: an appraisal of policy at home and abroad - Brown, J. Douglas; Harbison, Frederick (New Jersey, 1957)
In & the perspective of history, the twentieth century may become recognized as the Century of Science. The nineteenth century saw the mechanical and industrial arts. progress at a rapid pace, but it was not until scientific investigation replaced mechanical ingenuity that the pace of change in our material way of life accelerated to an almost explosive speed. Two great wars have already blackened the record of the first half of this century. It has been science that has made those wars more frightful, more all pervading, and more destructive of resources-both hu man and material-than any wars in history. Science has likewise helped to repair the losses of war and to enhance the flow of material benefits. It has proved an instrument for good or ill according to the masters it has served since science is but a means and not a goal in human aspirations. It would be more accurate, perhaps, to designate this century the century of the scientist, and of those translators of science into action, the research engineer and the industrial executive.